Effects of Chemo- and Radiation Therapy on Microsurgical Testicular Sperm Extraction for Men with Nonobstructive Azoospermia. Issue 3 (2nd September 2022) - Brant, Aaron; Punjani, Nahid; Zaninovic, Nikica; Palermo, Gianpiero D.; Rosenwaks, Zev; Schlegel, Peter N.
Abstract : Purpose: Men who survive cancer as children or young adults may have severe spermatogenic impairment with azoospermia requiring surgical sperm retrieval and assisted reproductive technologies. We assessed treatment outcomes from a large series of cancer patients with prior radiation and/or chemotherapy. Materials and Methods: Men with nonobstructive azoospermia who underwent initial microsurgical testicular sperm extraction from 1995–2020 from a high-volume surgeon at a single institution were identified. Those with a history of malignancy treated by radiation therapy and/or chemotherapy were included. The primary outcome was successful sperm retrieval. Results: A total of 106 men were evaluated, of whom 57 received chemotherapy and radiation, 44 received only chemotherapy and 5 received only radiation. Sperm retrieval was successful in 39 of 106 (37%) men, with higher likelihood of retrieval in men who received only chemotherapy compared to men who received chemotherapy and radiation (61% vs 18%, p <0.001). None of the 18 patients who received chemotherapy with radiation to the pelvis had successful sperm retrieval, compared to 26% of patients who received chemotherapy with extra-pelvic radiation (p=0.02). Conclusions: Chemotherapy and radiation for cancer may result in nonobstructive azoospermia that can be treated to allow fertility. However, pelvic radiation therapy is associated with the worst prognosis for successful treatment with microsurgical sperm retrieval and in vitro fertilization; we observed no cases of successful retrieval in men who received pelvic radiation therapy. These data are useful for pretreatment counseling, suggesting that men with prior radiation therapy may not be candidates for surgical sperm retrieval.